Microarray analysis to determine gene expression changes in zebrafish embryos - Ünal, İsmail; Beler, Merih; Cansız, Derya; Emekli Alturfan, Ebru (Humana Press Inc., 2024)
Chemical exposure in humans begins from the zygote stage and continues throughout the development of the embryo and the fetus. Zebrafish are one of the most powerful model organisms used in many research areas, including genetics, environmental toxicology, development, DNA damage and repair, cancer, and other diseases. Among the advantages that facilitate the use of zebrafish as a model for studies are features such as high homology with the human genome, small size, and high reproductive potential in short periods. The use of zebrafish embryos in research has increased rapidly due to their advantageous properties, including extrauterine development and the transparent feature of the embryos. However, there are thousands of genes that can be encountered in research, and in this case, the workforce is too much. This workload has been alleviated with the developed technologies. Microarray is one of these technologies. An important parameter in this assay is the RIN value. The RIN value ranges from 1 to 10, indicating mRNA degradation, and therefore helps to decide whether to continue the study. In this chapter, microarray analysis, which is one of the main techniques used in the determination of gene expression in zebrafish embryos, is described.
Keywords: cRNA; Microarray Analysis; RIN Values; Zebrafish Embryo